Influence of socio-demographic factors on the use of maternal health care among Muslim women in urban slums of Mumbai, India - Pinjari, Vahhida; Rakshase, Bal; Pardhi, Ashish (Indian Journal of Child Health, 2024)
Background: Low and middle-income countries such as India face significant challenges in improving maternal health and reducing maternal mortality rate. To combat this problem, it is essential to utilize maternal health-care services.Objective: This study aims to assess the utilization of maternal health-care services (Antenatal care [ANC] and skilled attendance at birth) and the determining factors of maternal health-care utilization.Materials and Methods: This study is cross-sectional. The study is carried out in an urban slum in Mumbai, India. The respondents were selected using a multistage sampling procedure, and 300 Muslim women who delivered in the past 2 years in the reproductive age group (15–49 years) were selected. The data were collected using a structured interview schedule. Data were analyzed using logistic regression analysis.Results: The study shows that maternal health-care utilization among respondents was unsatisfactory. Only 43.8% of the respondents utilized full ANC service and 27.3% still delivered at home with unskilled birth attendance (traditional Dai). A medical emergency, high cost, and lack of quality of services were the most common reasons to deliver at home. Respondents’ age at marriage, education (respondents and partners), monthly income, number of children, and type of family are the most important determining factors for the utilization of maternal health-care services.Conclusion: Better utilization of maternal health-care services can be achieved by improving the overall socioeconomic status of Muslim women. To improve maternal healthcare, special attention is required to be paid to the education of women and spouses. Furthermore, policies may address the women’s subordinate position in socioeconomic parameters. Similarly, close monitoring is required by the government through different agencies on the utilization of maternal health-care services.